Assessment of litter in the remote beaches of Lakshadweep Islands, Arabian Sea. (December 2020) - Kaviarasan, T.; Naik, Subrat; Sivadas, S.K.; Dhineka, K.; Sambandam, M.; Sivyer, David; Mishra, Pravakar; Ramana Murthy, M.V.
Abstract: The objective of this study was to obtain baseline data on litter from three beaches of the Lakshadweep Islands (Kadmat, Suheli Par, and Minicoy). At each site, three transects of 20 × 20 m of the foreshore and intertidal zone were sampled during low tide. All macro litter (size >2.5 cm to <1 m) within each transect were collected and counted. A total of 1231 litter items belonging to 22 categories were recorded. The highest average abundance (193 ± 97 items/400 m 2 ) of marine litter was found in Kadmat, followed by Suheli Par (154 ± 31items/400 m 2 ) and Minicoy (63 ± 49 items/400 m 2 ) islands. The Clean Coast Index (CCI) suggests that Minicoy Island has a clean beach (CCI 3.15) while Suheli Par (CCI 8) and Kadmat (CCI 10) were moderate. The primary contributing sources of litter on the beaches were fishing (45%) and public (34%). Better management practices are required to control litter sources. Highlights: Baseline data on abundance, composition and source of marine litter in remote beaches of Lakshadweep Island, Arabian Sea Litter belonging to 22 categories comprised mostly plastics (87%). Main contributing sources of litter are fishing (45%) and tourism (34%). Awareness and proper solid waste management is prerequisite for containing marine litter.